Insects Of Gunung Ledang, Johor, Malaysia - Mohamed, Maryati (Penerbit UTHM, 2017)
This book starts with an introductory overview of insects and entomotourism potential as new type of nature tourism in Gunung Ledang, Johor, Malaysia. The book is divided into four chapters from general information of common groups of insect until Orders to species name (if possible) of insects. This book is suitable for those who are interested in learning about insect in general.